Hydrogen production in photolysis of aqueous manganese(II) bicarbonate - Tennnakoon, K. and others (University of Peradeniya. Peradeniya, 1995)
Photolysis of an aqueous solution of manganese(II) bicarbonate is found to generate hydrogen with precipitation of Manganese (III) hydrous oxide. Manganese(III) hydrous oxide in turn is found to photoreduce water with concomitant oxidation to manganese dioxide. Reaction mechanisms are discussed.
Keywords: Chemistry; Irradiation; pH; Spectral analysis; Hydrogen; Photolysis; Aqueous manganese bicarbonate